2023
DOI: 10.1002/apj.2896
|View full text |Cite
|
Sign up to set email alerts
|

A short review on recent advances in porous adsorbents for separation of oxygen from atmospheric air

Abstract: Pure oxygen demand is continuously increasing worldwide due to wide applications including medical and industrial. Pressure swing adsorption (PSA) is one of the promising techniques to separate O 2 from atmospheric air. The porous solid adsorbent is a key element in the PSA to trap nitrogen (N 2 ) and release O 2 . Several adsorbents including low silica X (LSX), zeolite 5A, ionexchanged LSX (Li-LSX, AgLi-LSX, Ca-LSX), Engelhard titanosilicate (Na-ETS-10, Ag-ETS-10), and SSZ-13 have been investigated for adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…It is clear from the literature that the Ag-ETS-10 sorption affinity is increased in the order O 2 < Ar < N 2 . Recently, our group has reported the summary of potential adsorbents for O 2 purification from air and identified that Ag-ETS-10 is one of the potential sorbents for O 2 purification, which can remove Ar from air composition …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from the literature that the Ag-ETS-10 sorption affinity is increased in the order O 2 < Ar < N 2 . Recently, our group has reported the summary of potential adsorbents for O 2 purification from air and identified that Ag-ETS-10 is one of the potential sorbents for O 2 purification, which can remove Ar from air composition …”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has reported the summary of potential adsorbents for O 2 purification from air and identified that Ag-ETS-10 is one of the potential sorbents for O 2 purification, which can remove Ar from air composition. 28 Many researchers are still focusing on improving the adsorption capacity of N 2 and Ar for O 2 separation. Recently, Mousavi et al 29 reported on Ca 2+ ion-exchanged hierarchical 13X for N 2 sorption.…”
Section: Introductionmentioning
confidence: 99%